Tire Company’s Valuation in Using Free Cash Flow to Firm and Relative Valuation Method - Adrianov, Bobby; Hendrawan, Riko (International Journal Labs, 2023)
Tire company shares are considered to be the most prospective in 2018. This is related to the increasing level of tire exports, especially to Europe. Goodyear Indonesia (GDYR), Gajah Tunggal (GJTL), and Multistrada Arah Sarana (MASA) are three listed companies listed on the Indonesia Stock Exchange in 2014-2018. This thesis analyzes the intrinsic price of shares in the Tire Sub-Sector using the Discounted Cash Flow - Free Cash Flow to Firm (FCFF) Method and the Relative Valuation (RV) approach, so that interested parties or investors can assess how the third issuer's position shares. The basis of the estimation is an analysis of the financial statements of the three companies in the period 2014 to 2018, to conduct a fair valuation of shares in 2018 and an extension of the estimated share price in 2019. With the DCF-FCFF approach, the results show that GDYR shares are overvalued in all scenarios. GJTL's share price is also overvalued in the Optimistic and Moderate scenarios, but the Pessimistic scenario is overvalued. Meanwhile, MASA's share price is overvalued in all scenarios. With the PER approach, the results show that GDYR & MASA's shares are in an overvalued position in all scenarios. However, GJTL shares are in an overvalued position in all scenarios. With the PBV approach, the results show that the share price of GDYR & MASA are in an overvalued position in all scenarios. However, GJTL's share price is overvalued in all scenarios.